The relationship between enhanced dielectric property and structural distortion in Ca doped Ba2NaNb5O15 tungsten bronze ceramics. Issue 13 (October 2020) - Li, Run; Pu, Yongping; Zhang, Qianwen; Wang, Wen; Li, Jingwei; Du, Xinyi; Chen, Min; Zhang, Xian; Sun, Zixiong
Abstract: The relationship between enhanced dielectric property and structural distortion in tungsten bronze structure ceramics was discussed in this work. The ceramics with the composition of (Ba1- x Ca x )2 NaNb5 O15 ( x = 0, 0.1, 0.2, 0.3, 0.4) were fabricated via conventional solid-state method. All ceramics were pure without secondary phase and the distinct lattice distortion in structure was testified by Rietveld XRD refinement. Compared with the un-doped composition, the maximum polarization and energy storage density were strongly enhanced according to the ferroelectric property measurements, which were contributed to the distortion of NbO6 octahedron induced by the variation of ionic radius. The actually pulsed charge-discharge property of x = 0.3 ceramic was tested, whist excellent power density ( P D = 35.106 MV/cm 3 ) and discharge energy density ( W d = 0.29 J/cm 3 ) were obtained at 100 °C under 120 kV/cm, revealing the potential for application of Ba2 NaNb5 O15 system-based ceramics in harsh environment.